Molecular characterization of cellular stress responses during coronavirus infection - Fung, To Sing (2015)
Coronaviruses are important animal and human pathogens. In this study, two stress pathways – the unfolded protein response (UPR) and c-Jun N-terminal kinase (JNK) pathway are shown to be activated in cells infected with infectious bronchitis virus (IBV). The inositol requiring protein 1 (IRE1) branch of UPR protects infected cells from apoptosis by splicing the mRNA of X-box protein 1 (XBP1) and differentially modulating the activation of two kinases. The PKR-like ER protein kinase (PERK) branch of UPR promotes IBV-induced apoptosis by up-regulating C/EBP homologous protein (CHOP). JNK is phosphorylated by MKK7 during IBV infection, and it promotes apoptosis by modulating the level of B cell lymphoma-2 (Bcl2) family proteins. Moreover, IRE1 mediates autophagy induction whereas XBP1 and JNK contribute to the induction of pro-inflammatory cytokines (interleukin-8) and type-I interferon in the IBV-infected cells. Therefore, these stress pathways modulate critical cellular events and contribute to pathogenesis during coronavirus infection.